To the biology of the Damalacantha vacca (Fischer von Waldheim, 1846) (Orthoptera: Tettigonnidae: Bradyporinae) with the description of eggs - Temreshev, I. I. (Acta Biologica Sibirica, 2017)
The article gives a new data on the biology and fecundity of the grasshopper Damalacantha vacca (Fischer von Waldheim, 1846), a rare species of the Orthopterans, listed in the Red Book of the Republic of Kazakhstan. Earlier in the literature it was noted that this species eats saltwort (Salsola). When the Damalacantha vacca was kept in the cage, in addition to plant foods (except for Amaranthaceae and Chenopodiaceae plants, cereals, mostly spikelets and young leaves, and thinly sliced pieces of various vegetables - cabbage, potatoes, carrots) were eaten, and animals (dead grasshoppers, flies and butterflies - Owlet moths). Egg laying by females carried out in batches of 5-6 pieces per soil, with preference given to areas with compacted soil, permeated with interlaced plant roots. Fecundity of two females, who made a full clutch, was 49 and 54 eggs, respectively. For the first time the description of the egg is given and the structure of the chorion.